A theoretical study of the ability of 2D monolayer Au (111) to activate gas molecules. (23rd March 2021) - Lin, Long; Yan, Longbin; He, Chaozheng; Yao, Linwei; Xie, Kun; Chen, Ruixin; Zhu, Linghao; Huang, Jingtao; Sun, Jingwen; Zhu, Junwu; Zhang, Zhanying
Abstract: The adsorption and activation of gas molecules are investigated substantially in solid-gas heterogeneous catalysis. Here we investigated the interaction between gas molecules and unique two-dimensional monolayer Au (111) structure using density functional theory. It is found that CO2, H2 O, N2 and CH4 molecules are weakly adsorbed on the surface with the adsorption energies between −0.150 and −0.250 eV due to van der Waals interaction. While CO, NO, NO2, and NH3 molecules are adsorbed more stably with the adsorption energies between −0.300 and −0.470 eV. Especially, the bond length of CO is stretched by 0.038 Å and the bond angle of NO2 is obviously enlarged by 10.460°. The activation originates from the rearrangement of molecule orbitals and the orbitals hybridization between the partial orbitals of gas molecules and Au-5 d orbitals. The fundamental analyses of adsorption mechanism and electronic properties may provide guidance for the applications of two-dimensional monolayer metal catalysis. PACSnumbers 73.22.-f, 73.61.-r Graphical abstract: Image 1 Highlights: The adsorption behavior of a series of small gas molecules on monolayer Au (111) surface are investigated systematically. The CO, NO2 can be activated by the Au (111) surface. The monolayer Au (111) surface may have a better interaction with gas molecules than multilayer Au (111) surface.